2014
DOI: 10.1093/hmg/ddu732
|View full text |Cite
|
Sign up to set email alerts
|

A genetic association study of activated partial thromboplastin time in European Americans and African Americans: the ARIC Study

Abstract: Reduced activated partial thromboplastin time (aPTT) is a risk marker for incident and recurrent venous thromboembolism (VTE). Genetic factors influencing aPTT are not well understood, especially in populations of non-European ancestry. The present study aimed to identify aPTT-related gene variants in both European Americans (EAs) and African Americans (AAs). We conducted a genetic association study for aPTT in 9719 EAs and 2799 AAs from the Atherosclerosis Risk in Communities (ARIC) study. Using the Candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
(70 reference statements)
0
13
0
1
Order By: Relevance
“…The maternity center is located in a small city in China that has relatively few population migrations, and most of the participants in this study were local residents. As previously reported [34] , the influence of ethnicity on coagulation might exist that could be excluded in our study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The maternity center is located in a small city in China that has relatively few population migrations, and most of the participants in this study were local residents. As previously reported [34] , the influence of ethnicity on coagulation might exist that could be excluded in our study.…”
Section: Discussionmentioning
confidence: 81%
“…The shortening of APTT in type 2 diabetic patients has been described as indicating a high risk of a hypercoagulable state [31] . It has also been shown that the increase in fibrinogen and the reduction in fibrinolytic activity in GDM are more similar to the changes present in type 2 than in type 1 diabetic patients [32] , and it is thought that a shorter APTT is a marker of venous thromboembolism risk [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have indicated that they may interact with each other in the coagulation pathway. KNG1 and HRG have similar structures and are adjacent to each other on chromosome 3, which suggests that these proteins may exhibit similar functions ( 24 , 25 ). HRG deficiency is associated with enhanced blood coagulation, which indicates that decreased KNG1 is a potential cofactor to enhance coagulation ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The shortening of APTT in type 2 diabetic patients has been described as indicating a high risk of a hypercoagulable state [29] . It has also been shown that the increase in fibrinogen and the reduction in fibrinolytic activity in GDM are more similar to the changes present in type 2 than in type 1 diabetic patients [30] , and it is thought that a shorter APTT is a marker of venous thromboembolism risk [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…The maternity center is located in a small city in China that has relatively small population mobility, and most of the participants in the study were local residents. These characteristics of the study participants exclude the influence of ethnicity on coagulation that has been previously reported [32] . In addition, we used different methods to assess CFA at the same time point and the results were consistent.…”
Section: Discussionmentioning
confidence: 99%